PERCEPATAN PENYELESAIAN KASUS PERTANAHAN SEBAGAI SALAH SATU TUJUAN PENGELOLAAN PERTANAHAN - Anak Agung Ayu Intan Puspadewi (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2022)
Land cases in Indonesia still often occur, many land cases have not been resolved properly, so as one of the land settlements an accelerated settlement is carried out based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases. The problems that will be discussed are classifying the types of land cases and steps to accelerate the settlement of land cases in Indonesia. To answer these problems, this paper uses research methods, namely normative research types, using a law, analysis and concept approach. The sources of legal materials used were primary, secondary and tertiary, and the techniques of collecting legal materials used were descriptive and systematic. The conclusion in this paper is the classification of three types of land cases, namely conflicts, disputes, and cases. conflicts and conflicts are classified into severe cases, moderate cases and mild cases. Steps to accelerate the settlement of land settlements based on Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 can be settled directly by way of deliberation and settlement through the Judiciary. Land cases are resolved starting with complaints through the reception counter for complaints made and carried out by the Ministry, regional offices and land offices. disputes and conflicts are carried out through several stages, namely, case studies, initial degrees, research, exposure of research results, coordination meetings, final degrees, and case settlements.Keywords: , land cases; land management; settlement of land cases